2002
DOI: 10.1038/sj.bjc.6600197
|View full text |Cite
|
Sign up to set email alerts
|

The cancer preventative agent resveratrol is converted to the anticancer agent piceatannol by the cytochrome P450 enzyme CYP1B1

Abstract: Resveratrol is a cancer preventative agent that is found in red wine. Piceatannol is a closely related stilbene that has antileukaemic activity and is also a tyrosine kinase inhibitor. Piceatannol differs from resveratrol by having an additional aromatic hydroxy group. The enzyme CYP1B1 is overexpressed in a wide variety of human tumours and catalyses aromatic hydroxylation reactions. We report here that the cancer preventative agent resveratrol undergoes metabolism by the cytochrome P450 enzyme CYP1B1 to give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
203
2
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(223 citation statements)
references
References 25 publications
(21 reference statements)
5
203
2
5
Order By: Relevance
“…It is conceivable that piceatannol was present at very low levels, which might have confounded detection by the procedures used here. The ability to convert resveratrol to piceatannol has been surmised to be a relatively specific property of CYP1B1 (Potter et al, 2002b). The lack of the presence of piceatannol at detectable concentrations in our study in the mouse is consistent with the notion that CYP1B1 is not expressed at appreciable levels in mouse liver .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is conceivable that piceatannol was present at very low levels, which might have confounded detection by the procedures used here. The ability to convert resveratrol to piceatannol has been surmised to be a relatively specific property of CYP1B1 (Potter et al, 2002b). The lack of the presence of piceatannol at detectable concentrations in our study in the mouse is consistent with the notion that CYP1B1 is not expressed at appreciable levels in mouse liver .…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with the results of recent in vitro experiments using cytochrome P450 isoenzyme preparations, in which DMU 212 was found to undergo both aromatic hydroxylation and O-demethylation reactions primarily catalysed by isoenzymes of the CYP1 family (Wilsher et al, unpublished). In analogy, resveratrol was recently found to undergo metabolic oxidation in vitro to piceatannol (3,5,2 0 ,4 0 -tetra-hydroxystilbene), when incubated with a source of CYP1B1 (Potter et al, 2002b). In the study described here, piceatannol was not identified as a metabolite of resveratrol in mice in vivo or in mouse liver microsomes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, UV irradiation has been demonstrated to produce large amounts of piceatannol in callus of peanut (40). Piceatannol is also found in resveratrol-treated cells when resveratrol is metabolized by cytochrome P450 enzyme CYP1B1 (41). Despite the well documented beneficial function of resveratrol in chemoprevention and lowering the risk of chronic diseases, including obesity (24,25), the role of piceatannol in the aforementioned diseases has not yet been resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Potter successfully converted resveratrol into piceatannol by the cytochrome P450 enzyme CYP1B1 which is overexpressed in a wide variety of human tumours and catalyses aromatic hydroxylation reactions. This observation demonstrates that a natural dietary cancer preventative agent, resveratrol, can be converted to piceatannol with known anti-cancer activity by P450 enzyme CYP1B1 so as to have the effect of anticancer (Potter et al, 2002). On the other hand, others focus their full attention on researching the pathways of biotransformation so as to explore the mechanisms of microorganisms and enzymes how to producing anticancer compounds.…”
Section: To Investigate Correlative Mechanismmentioning
confidence: 97%